The mindful investor : how a calm mind can bring you inner peace and financial security - Gonzalez, Maria, 1958- (J. Wiley, 2010)
"Money. The word itself has a power of its own. It can induce feelings and start a train of thought instantly. Unfortunately, often these feelings and thoughts are negative and stressful. We believe that achieving a healthy relationship with money is necessary because it's attached, in some way, to almost every aspect of our lives. In reality, most people have enough money, even after the recent market collapse. What they don't have is the level of calm, clarity, and focus required to live peacefully with money. Mindfulness can help achieve it. The Mindful Investor is an indispensable guide for individual investors, business people, and professionals who are looking for a better way to manage their money"--Preface.